Catalyzing Singlet Fission by Transition Metals: Second versus Third Row Effects - Hou, Yuxuan; Papadopoulos, Ilias; Bo, Yifan; Wollny, Anna-Sophie; Ferguson, Michael J.; Mai, Lukas A.; Tykwinski, Rik R.; Guldi, Dirk M. (Precision Chemistry, 2023)
The synthesis and characterization of platinum(II) and palladium(II) complexes bearing two (dimers Pt(Lpc)2Cl2 and Pd(Lpc)2Cl2), one (monomers Pt(Lpc)(Lref)Cl2 and Pd(Lpc)(Lref)Cl2), or no (reference compounds Pt(Lref)2Cl2 and Pd(Lref)2Cl2) pentacene-based pyridyl ligands are presented. Photophysical properties of the dimers are probed by means of steady-state and time-resolved transient absorption measurements in comparison to the monomer and model compounds. Our results document that despite enhanced spin–orbit coupling from the presence of heavy atoms, intramolecular singlet fission (iSF) is not challenged by intersystem crossing. iSF thus yields correlated triplet pairs and even uncorrelated triplet excited states upon decoherence. Importantly, significant separation of the two pentacenyl groups facilitates decoupling of the two chromophores. Furthermore, the mechanism of iSF is altered depending on the respective metal center, that is, Pt(II) versus Pd(II). The dimer based on Pt(II), Pt(Lpc)2Cl2, exhibits a direct pathway for the iSF and forms a correlated triplet pair with singlet–quintet spin-mixing within 10 ns in variable solvents. On the other hand, the dimer based on Pd(II), Pd(Lpc)2Cl2, leads to charge transfer mixing during the population of the correlated triplet pair that is dependent on solvent polarity. Moreover, Pd(Lpc)2Cl2 gives rise to a stable equilibrium between singlet and quintet correlated triplet pairs with lifetimes of up to 170 ns. Inherent differences in the size and polarizability, when contrasting platinum(II) with palladium(II), are the most likely rationale for the underlying trends.